Effect of Nerium oleander (N.O.) Leaves Extract on Serum hepcidin, Total Iron, and Infiltration of ED1 Positive Cells in Albino Rat. (31st August 2013) - Abbasi, Muddasir Hassan; Fatima, Sana; Naz, Naila; Malik, Ihtzaz A.; Sheikh, Nadeem
Abstract : To gain insight into the hepatohistological alterations in noninjured rat liver, Nerium oleander (N.O.) leaves extract was injected intramuscularly to induce an acute phase reaction (APR). Histopathological changes were studied after 3, 12, and 24 h time course of sterile muscle abscess. Tissue integrity and any infiltration of inflammatory cells in the liver were investigated by Hematoxylin and Eosin and ED1 peroxidase stainings. The administration of N.O. leaves extract (10 mL/kg) in H & E stained sections showed a general vacuolization of cytoplasm resulting loss of polarity with prominent nucleoli after 3 h of induction. At 12 h, eccentric nuclei were also observed in the sections. Marked infiltration of leucocytes with predominate macrophages was also found after 24 h as seen by ED1 positive staining. In the present study, a possible relationship between serum hepcidin and total iron level was also investigated in vivo . An early increase of hepcidin and total iron level (3 h) with a maximum at 12 h (P < 0.01 ; P < 0.001 ) was observed. These changes indicate that sterile muscle abscess may induce APR resulting in hepatic damage which is evident with the recruitment of inflammatory cells into the organ.